2015
DOI: 10.7860/jcdr/2015/14648.6659
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Evaluation of Patient’s Satisfaction and Comfort Level by Diode Laser and Scalpel in the Management of Mucogingival Anomalies

Abstract: Laser is a desirable therapeutic alternative to correct soft tissue anomalies. It allows good control of haemorrhage with comfortable healing phase and appreciable satisfactory outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…A total of 4989 studies with relevant titles were further scrutinized based on eligibility criteria. After removing studies on basis of irrelevant objective, protocols only, no abstract, no full text, in vitro studies, different study designs, only 25 studies[12131421222324252627282930313233343536373839404142] were finally selected to be included for data extraction. The PRISMA flow chart of the process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 4989 studies with relevant titles were further scrutinized based on eligibility criteria. After removing studies on basis of irrelevant objective, protocols only, no abstract, no full text, in vitro studies, different study designs, only 25 studies[12131421222324252627282930313233343536373839404142] were finally selected to be included for data extraction. The PRISMA flow chart of the process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies reported gender distribution of patients except Gera et al ., Kumar et al . [25] and Basha et al . [23] Minimum follow-up was of 24 h, and the maximum follow-up was of 15 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37][38] Recently, Farista et al demonstrated that diode laser decreased VAS scores significantly than conventional surgery in crown lengthening. 36 In a study evaluating the effect of diode laser on depigmentation, El Shenawy et al stated that diode laser can be used as a safe and effective treatment modality to provide optimal aesthetics with reduced discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported less postoperative pain and discomfort and also reduction in use of analgesics and local anesthetic drugs in laser surgery. [16][17][18] However, there are still some disadvantages in regard to adjunctive laser treatment in orthodontics. Application of laser is limited due to the high cost of laser devices.…”
Section: Introductionmentioning
confidence: 99%